A Nonadjuvanted Whole-Inactivated Pneumococcal Vaccine Induces Multiserotype Opsonophagocytic Responses Mediated by Noncapsule-Specific Antibodies - Shannon C. David; Erin B. Brazel; Eve V. Singleton; Vikrant Minhas; Zoe Laan; Catherine Scougall; Austen Y. Chen; Hui Wang; Chloe J. Gates; Kimberley T. McLean; Jeremy S. Brown; Giuseppe Ercoli; et al. (mBio, 2022)
ABSTRACT Streptococcus pneumoniae (Spn) remains a major cause of global mortality, with extensive antigenic diversity between capsular serotypes that poses an ongoing challenge for vaccine development. Widespread use of pneumococcal conjugate vaccines (PCVs) targeting Spn capsules has greatly reduced infections by vaccine-included serotypes but has led to increased infections by nonincluded serotypes. To date, high cost of PCVs has also limited their usefulness in low-income regions where disease burdens are highest. To overcome these limitations, serotype-independent vaccines are being actively researched. We have developed a whole-cell gamma-irradiated Spn vaccine (termed Gamma-PN) providing serotype-independent protection. We demonstrate that Gamma-PN immunization of mice or rabbits via the clinically relevant intramuscular route induces protein-specific antibodies able to bind numerous nonvaccine encapsulated serotypes, which mediate opsonophagocytic killing and protection against lethal challenges. Gamma-PN induced comparable or superior opsonophagocytic killing assay (OPKA) responses in rabbits to the licensed Prevnar 13 vaccine (PCV13) for vaccine-included serotypes, and a superior response to nonincluded serotypes, including emergent 22F and 35B. Additionally, despite a lower observed reactogenicity, administration of Gamma-PN without adjuvant resulted in higher OPKA responses and improved protection compared to adjuvanted Gamma-PN. To our knowledge, this has not been demonstrated previously for a whole-inactivated Spn vaccine. Eliminating the requirement for adjuvant comes with numerous benefits for clinical applications of this vaccine and poses interesting questions for the inclusion of adjuvant in similar vaccines in development. IMPORTANCE The target pathogen of this study, Streptococcus pneumoniae, kills over 300,000 children <5 years of age every single year, and is the leading cause of pneumonia-associated mortality globally. While the capsular polysaccharide (CPS)-based vaccine Prevnar13 prevents serious illness caused by 13 serotypes, ongoing Prevnar13 use has driven the emergence of nonincluded serotypes as major causes of infection and disease. To overcome this issue, we have developed a next-generation pneumococcal vaccine conferring serotype-independent protection. This vaccine shows equivalent or superior efficacy to Prevnar13, and performance was heightened when our vaccine was administered with no adjuvant. These findings should be considered for similar vaccines in development, as the benefit of adjuvant is often assumed and its automatic inclusion may be limiting product efficacy, resulting in potential abandonment of viable vaccine candidates, or prolonging their time to clinic.